A New Look at the Processes of Edema Formation of the Recipient Wound Bed and the Possibility of Its Assessment Using Modern Instrumental Diagnostic Methods in Experiment and Clinical Practice - I. V. Pavlenko; M. S. Baleev; V. N. Gostev (Неотложная медицинская помощь)
The complete closure of extensive wound defects is a serious problem of modern surgery. In a significant part of clinical cases, practicing surgeons have difficulties in the surgical treatment for extensive soft tissue wounds, especially those that have existed for a long time and have no tendency to heal. Split skin grafting is the operation of choice when closing chronic wounds, as it has a number of advantages over other options for skin plastic surgery. At the same time, the percentage of splitskin graft engraftment depends on the state of the recipient bed in most cases, the degree of which is determined by such mutually influencing processes as inosculation, angio and vasculogenesis (angiogenesis regulator), occurring simultaneously in the graft itself and the receiving wound bed. The review presents studies by domestic and foreign authors concerning new possibilities of instrumental assessment of the condition of the recipient wound bed, namely the degree of its edema. The results of scientific papers describing the relationship between the degree of swelling of the wound and the result of its plastic closure are shown. The features of modern methods of optical bioimaging are revealed when they are used in determining the amount of fluid in soft tissue wounds both in experiment and clinical practice.